Slapface [videorecording (DVD)] - Kipp, Jeremiah; Manning, Mike C., 1987-; Maturo, August; Barer, Libe, 1991-; Lee, Mirabelle; D'Ambrosio, Bianca; D'Ambrosio, Chiara; Hassel, Lukas; Hedaya, Dan (Shudder, 2022)
After the death of his mother, Lucas, a loner who lives in a rundown home with his brother Tom, regularly seeks solace in the nearby woods. With his only "friends" being a group of female bullies, he keeps to himself most of the time. But, after a strange encounter with an inhuman monster, Lucas begins to withdraw from others. When the two reach a tentative trust, a bizarre friendship is born, and Lucas is swept up in a series of primal adventures.